Batasan Umur dalam Perkawinan Berdasarkan Hukum (Lex Jurnalica, 2015)
AbstractIn Act 1 of 1974 the restrictions on the age of the marriage age 19 years old groom and the bride's age of 16 years. For that, it must be prevented the marriage between husband and wife who are minors. Age limit for marriage can be defined as a marriage performed by people who had not yet reached the age of marriage. This marriage can only take place legitimately to be carried out, but by meeting the requirements tertentu.Terkait the age limit in marriage while the problem in this research is how the age limit to perform a marriage in a legal perspective, as well as the legal consequences of the marriage How minors. The research method used Normative research and literature study covering the primary legal materials, secondary, and tertiary, and wear descriptive research approach is qualitative analysis techniques. The conclusion is in the perspective of the law, the legal difference marriage is restricted by age yitu men 19 years and women 16 year, as mentioned in the law No.1 of 1974 on marriage. As gender equality so that the age of marriage is no longer differentiated between men and women must specify an age limit which same. Marriage of minors can be done by first doing dispensation. If no exemption then the marriage can be prevented or canceled. Prevention happen if there are parties who do not qualify to enter into marriage. Cancellation ensued if the marriage does not fulfill the terms of marriage or considered invalid, only then can the marriage was annulled after submitted to the court. Keywords: marriage, age restrictions, the law AbstrakDalam UU No.1 Tahun 1974 adanya pembatasan usia perkawinan yakni usia calon mempelai pria 19 tahun dan usia calon mempelai wanita 16 tahun. Untuk itu, harus dicegah adanya perkawinan antara suami istri yang masih di bawah umur. Batasan umur dalam perkawinan bisa diartikan sebagai perkawinan yang dilakukan oleh orang yang belum memasuki usia perkawinan. Perkawinan ini dapat saja sah berlangsung untuk dilaksanakan, namun dengan memenuhi persyaratan-persyaratan tertentu.Terkait dengan Batasan umur dalam perkawinan adapun permasalahan dalam penelitian ini adalah Bagaimana batasan umur untuk melakukan perkawinan dalam perspektif hukum, serta Bagaimanakah akibat hukum terhadap perkawinan dibawah umur. Metode penelitian menggunakan penelitian Normatif dan Studi Kepustakaan yang meliputi bahan hukum primer, sekunder, dan tersier, dan memakai Pendekatan Penelitian deskriptif Teknik analisis bersifat kualitatif. Kesimpulan yang diperoleh adalah dalam perspektif hukum, perbedaan hukum perkawinan dibatasi oleh usia yitu laki-laki 19 tahun dan perempuan 16 tahun,sebagaimana tersebut dalam undang-undang No.1 tahun 1974 tentang perkawinan. Seiring kesetaraan gender sehingga usia perkawinan tidak lagi dibedakan antara laki-laki dan perempuan harus di tentukan suatu batasan umur yang sama. Perkawinan dibawah umur bisa dilakukan dengan terlebih dahulu melakukan dispensasi. Jika tidak ada dispensasi maka perkawinan dapat dicegah atau dibatalkan. Pencegahan terjadi jika ada pihak-pihak yang tidak memenuhi syarat untuk melangsungkan perkawinan. Pembatalan pun terjadi jika perkawinan tersebut tidak memenuhi syarat-syarat perkawinan atau di anggap tidak sah, maka barulah perkawinan itu dibatalkan sesudah di ajukan ke muka pengadilan. Kata kunci: perkawinan, batasan umur, hukum